ANALISANDO A PRODUÇÃO TEXTUAL DOS DISCENTES DO PROFIS-UNICAMP: O CASO DO GÊNERO "RESUMO ACADÊMICO". - Bentes, Anna Christina; de Paula Alves, Beatriz (Trabalhos em Lingüística Aplicada, 2025)
In higher education, the abstract is usually understood as a genre of scientific dissemination that deals with the content and structure of a given source text in a short paragraph (Motta-Roth and Hendges, 2010). In basic education, although the activities of interpreting, understanding and summarizing texts are very present in the teaching of the most diverse school subjects, students, when entering the university environment, face challenges to fully comply with the particularities of these practices under a new production situation. The objective of this work is to analyze, based on studies of Textual Linguistics, thirty-seven productions of the academic summary genre by students of the Interdisciplinary Higher Education Program (ProFIS) of the State University of Campinas (Unicamp), in the context of the discipline Reading and Production of Academic Texts I. The results demonstrate the process of appropriation of knowledge related, in this case, to the compositional structure and retextualization to fulfill the purpose of the academic summary. These results demand reflection on the teaching of literacies characteristic of academia, especially with regard to the adaptation of new students to the required textual practices.